62 Feeding Chicory-plantain Silage and Se-yeast to Lactating Ewes Subjected to Intramammary Infection: Effect on the Immune System. (8th October 2021) - Ford, Hunter; Bionaz, Massimo; Ates, Serkan; Klopfenstein, Joe; Vanegas, Jorge; Busato, Sebastiano; Hasan, Daniella; Park, Shelby; Pearce, Carolyn; Quinones, Tyler; Ness, Kate; Torres, Mariangel Aleman
Abstract: The objective was to test the effect on the immune status by feeding a combination of chicory-plantain and Se-yeast in lactating ewes subjected to intramammary infection (IMI) with 2×107CFU of Strep uberis in both glands. For the purpose we enrolled 28 Polypay lactating sheep from a prior study where they were randomly allocated to receive chicory (CS) or grass (GC) silage and either 3.6 mg of Se/day as Se-yeast (DiaMune, Diamond V) (Y) or isoenergetic-isonitrogenous alfalfa meal (C) for 2 months. For the present study, ewes were kept on the original dietary regiment except the CT group received a chicory-plantain silage(50% each). Blood was collected prior to and for 10 days after IMI for a complete blood count(VetScan HM5), leukocytes migration, and rectal temperature (RT). Data were analyzed using GLIMMIX (SAS)with time, silage type, and Se and their interactions as the fixed effects and ewe as random effect with significance declared at P ≤ 0.05. RT was lower in chicory vs. grass before IMI and Se limited the RT increase after IMI. Total WBC levels tended (P = 0.06) to increase in animals fed with Se after IMI, which was driven by a larger number of lymphocytes. Hematocrit, red blood cells, and hemoglobin were strongly decreased by IMI. The mean cell volume was overall larger in ewes fed with chicory-plantain silage while mean cell hemoglobin was larger in animal fed with grass silage. The platelet distribution width was affected by silage*Se interaction due to a positive effect by Se in grass-fed but negative in chicory-plantain-fed ewes. Migration of neutrophils was larger in animals fed with chicory-plantain before IMI but similar between groups after IMI. Overall, these findings indicate that Se supplementation can increase lymphocytes with no effect on neutrophils while activity of neutrophils is positively affected by feeding chicory-plantain silage.